Responses of grassland birds and butterflies to control of sericea lespedeza with fire and grazing - Ogden, Sarah B. (Kansas State University, 2017)
Sericea lespedeza (Lespedeza cuneata) is an invasive forb that reduces native grass and forb abundance in tall-grass prairie by up to 92%. Controlling invasions is difficult because traditional land management tools used in the Flint Hills, broad spectrum herbicides, spring prescribed fire, and cattle grazing, are ineffective against sericea. Recent research has demonstrated, however, that mid- and late summer prescribed fire and spring fire with early season grazing by steers followed by late season grazing by sheep are effective at reducing sericea whole plant mass, number of seeds produced, and seed mass. Field results were from two separate experiments conducted in tall-grass prairie study sites in the Flint Hills. On a Geary County, Kansas, study site, the utility of 1) spring fire (control), 2) mid-summer fire, and 3) late summer fire on sericea control were compared. On a Woodson County, Kansas, study site, the utility of 1) spring fire with early season steer grazing followed by rest (control) and 2) spring fire with early season steer grazing and late season sheep grazing on sericea control were compared. At the same study sites, I measured responses by the native wildlife community to use of summer fire and sheep grazing, relative to their controls, to manage sericea lespedeza. Specifically, my objectives were to compare grassland songbird density, grassland songbird nest survival, and grassland butterfly species composition and density among treatments at both study sites. I also related patterns in the vegetation community of each treatment for each study site to respective patterns in grassland bird and butterfly communities. Within study sites, density, nest density, and nest success of grassland bird communities responded similarly to treatments and controls, with the exception that densities of Grasshopper Sparrows (Ammodramus savanarrum) were 3.4- and 2.2-fold greater in mid- and late summer fire plots than spring fire plots, respectively, in the Geary County study site. Species compositions of butterfly communities were similar across treatments within experiments, but grassland specialist species comprised only 8.6 and 1.2% of all butterfly observations in the Geary County and Woodson County experiments, respectively. Grassland specialist butterfly species may benefit from summer fire, as their nectar sources were more abundant in Summer Fire plots than Spring Fire plots. Overall, within each experiment, grassland bird and butterfly communities were similar across treatments, suggesting that treatments did not negatively affect grassland songbird and butterfly communities. I additionally demonstrated that Dickcissel (Spiza americana) nest sites contain a lower proportion of sericea than random points, the first evidence that the invasion is detrimental to grassland songbird species. Lacking control, the continued sericea invasion will out compete cumulatively more forb plants resulting in declining quality of grassland bird nesting habitat on the landscape. Controlling sericea lespedeza invasions will allow native forb species to increase in abundance and improve the condition of grasslands for native wildlife and livestock producers. Therefore, I advocate use of summer fire or spring fire with a combination of cattle and sheep grazing to control sericea lespedeza with the long-term goal of tall-grass prairie restoration.
Keywords: grassland birds; butterflies; sericea lespedeza; prescribed fire; grazing; tallgrass prairie